Pengaruh Rasio Likuiditas, Rasio Profitabilitas, Dan Aktiva Produktif Terhadap Pertumbuhan Sisa Hasil Usaha Koperasi Simpan Pinjam Di Kecamatan Sukawati - I Wayan Tegar Baskara; Ni Putu Yuria Mendra; Desak Ayu Sriary Bhegawati (Widya Manajemen, 2020)
The remaining operating income represents the income earned by the cooperative in one fiscal year less depreciation, costs, and other obligations including tax in the relevant fiscal year. The remaining results of operations are business profits that are divided according to the economic activities of cooperative members. This study aims to reexamine the effect of liquidity ratios, profitability ratios, and productive assets on the growth of the remaining operating results (SHU) of savings and loan cooperatives in Sukawati District. The sample in this study was 12 cooperatives in Sukawati Subdistrict using financial data for 3 consecutive years from 2016 to 2018. So, the total sample was 36. The sampling technique used in this study was purposive sampling. The analytical tool used is multiple linear regression analysis, classic assumption test, and goodness of fit test. The results showed that liquidity ratios and profitability ratios did not affect the growth of the remaining business results (SHU) of savings and loan cooperatives in Sukawati District, while the productive assets had a positive effect on the growth of the remaining business results (SHU) of savings and loan cooperatives in Sukawati District.